Why do plants silicify?. (March 2023) - de Tombeur, Félix; Raven, John A.; Toussaint, Aurèle; Lambers, Hans; Cooke, Julia; Hartley, Sue E.; Johnson, Scott N.; Coq, Sylvain; Katz, Ofir; Schaller, Jörg; Violle, Cyrille
Abstract: Despite seminal papers that stress the significance of silicon (Si) in plant biology and ecology, most studies focus on manipulations of Si supply and mitigation of stresses. The ecological significance of Si varies with different levels of biological organization, and remains hard to capture. We show that the costs of Si accumulation are greater than is currently acknowledged, and discuss potential links between Si and fitness components (growth, survival, reproduction), environment, and ecosystem functioning. We suggest that Si is more important in trait-based ecology than is currently recognized. Si potentially plays a significant role in many aspects of plant ecology, but knowledge gaps prevent us from understanding its possible contribution to the success of some clades and the expansion of specific biomes. Highlights: The significance of silicon (Si) in plant ecology remains elusive. Trait-based analyses show that Si accumulates most in leaves of small non-woody species and is linked to key functional traits, suggesting trade-offs and physiological constraints on the evolution of Si accumulation in plants. Plant Si-related functions affect fitness components (growth, survival, reproduction), but a sound understanding of Si–fitness relationships is missing. In grasses, there is evidence for a Si-mediated trade-off between growth and defense. Si accumulation is more expensive than is currently acknowledged, and cost–benefit analyses are pivotal to understand how variation is dependent on environment and on trade-offs with other traits. Si plays a significant role in many aspects of plant ecology, but major gaps prevent us from understanding why this trait has been selected for and has contributed to the success of specific clades.